3D meso-scale fracture modelling and validation of concrete based on in-situ X-ray Computed Tomography images using damage plasticity model. (15th August 2015) - Huang, Yujie; Yang, Zhenjun; Ren, Wenyuan; Liu, Guohua; Zhang, Chuanzeng
Abstract: Three-dimensional (3D) meso-scale finite element models of concrete based on in-situ X-ray Computed Tomography (XCT) images are developed and validated in this study. The micro-scale images from a Brazilian-like XCT test are first compressed and then transformed into manageable meso-scale 3D meshes using a voxel hexahedron meshing technique with a stacking algorithm. The continuum damage plasticity model is used to simulate complicated damage and fracture behaviour. Excellent qualitative agreement is found between modelling and the XCT compression test in terms of damage evolution and fracture process on both the surface and interior of the specimen. 3D uniaxial tension tests are also simulated, and it is found that the distribution of voids have profound influences on the strength and crack patterns. The image-based 3D models are proved very promising in elucidating fundamental mechanisms of complicated crack initiation and propagation behaviour that 2D studies are incapable of modelling.